INVESTIGATION OF THE RELATIONS BETWEEN CORONAVIRUS PHOBIA AND QUALITY OF LIFE OF CARE-GIVER NURSES DURING THE COVID-19 PANDEMIC: A SECTIONAL STUDY - v, Sümeyra Mihrap; SEVEN, Ahmet; ÇİL, Burak (Göbeklitepe Medical Science Journal, 2022)
The present study was conducted to examine the Coronavirus phobia and quality of life of nurses providing care during the COVID-19 pandemic period.The study was conducted descriptively and cross-sectionally with 178 nurses, who worked in a university hospital, and who agreed to participate in the study. The data were collected with a questionnaire that contained data on socio-demographic characteristics, Short Form 36 Quality of Life Scale, Coronavirus-19 Phobia Scale, and online google forms. The analysis of the data in computer medium was made by using percentages, mean values, and parametric and nonparametric tests.The Coronavirus phobia levels of women, married people, and those who had children were found to be higher at statistically significant levels in the study (p<0.05). The mean score of the nurses’ Coronavirus phobia scale was found to be 68.93±5.43. Also, no significant relations were detected between the subdimensions of the quality of life scale and Coronavirus phobia levels. (p>0.05).It was determined in the study that the quality of life of the nurses during the pandemic period was moderate, and the level of Coronavirus phobia was high. No correlations were detected between nurses’ quality of life and Coronavirus phobia levels.